An agent‐based simulation model of Eldana saccharina Walker. (15th December 2017) - van Vuuren, B.J.; Potgieter, L.; van Vuuren, J.H.
Abstract : Abstract: Eldana saccharina Walker (Lepidoptera: Pyralidae) is a stalk borer pest plaguing the sugar producing industry in South Africa . The pest feeds on the internal tissue of sugarcane stalks, causing yield losses in sucrose. Various control methods have been proposed in an attempt to suppress the pest. These control methods are, however, often difficult and costly to test, implement, and develop further in an iterative manner. In an attempt to better understand the behavior and population dynamics of E. saccharina, an agent‐based simulation model is presented in this paper which simulates the stalk borer's biology, feeding habits, mating behavior, dispersal patterns, and various other characteristics as accurately as possible. The flexibility and validity of the model are then ascertained by subjecting the model to expert opinion and parameter variation analysis. A simplified control measure is then implemented in order to demonstrate the possibility for using the agent‐based model in the future for developing and testing integrated pest management strategies against E. saccharina . Recommendations for Resource Managers: The use of agent‐based simulation modeling is investigated as a possible means for accurate capturing of the behavior of E. saccharina . The ability to accurately recreate pest behavior poses the opportunity for the detailed testing and development of control strategies to combat this sugarcane pest. By employing simulation modeling, control strategies may be tested to assess their anticipated success in eradicating the pest. The speed with which long‐term analyses may be conducted, as well as the absence of the associated cost of infield testing, means that various scenarios may be investigated over a number of iterations in an attempt to optimize the process and achieve maximum confidence prior to infield implementation of the control strategies. The successful implementation of this science may provide a platform to extend this type of modeling to include other pests and/or plant hosts which may benefit from pest suppression.